What is the intrinsic value of fertilizer? Experimental value elicitation and decomposition in the hill and terai regions of Nepal - Ward, Patrick S.; Gupta, Shweta; Singh, Vartika; Ortega, David L.; Gautam, Shriniwas; Guerena, David; Shrestha, Rudra Bahadur (International Food Policy Research Institute, 2019)
The government in Nepal faces double burden of enhancing fertilizer application rates in the country by investing in efforts to boost demand and at the same time, managing its dependence on global markets to fulfill the supply of important nutrients such as Urea and DAP. Without an understanding of the true valuation of fertilizers for farmers, achieving this balance would be difficult. We use Becker-DeGroot-Marshak value elicitation methods to derive the intrinsic value that farmers in Nepal place on fertilizers. Eliciting values under three distinct procurement scenarios, we are able to decompose the total intrinsic value of fertilizer into a willingness-to-pay (WTP) to travel to procure fertilizer, a WTP for assured fertilizer supplies, and a WTP for the productivity benefits of fertilizer. Disaggregating our sample according to location (hills versus terai), we are able to estimate differences in total intrinsic value as well as value components along these geographical dimensions. While farmers in the hills are generally willing to pay more for urea than their counterparts in the terai, the total amount they are willing to pay is, on average, less than the market price for urea. We explore heterogeneity in valuations and discuss the implications of our findings on fertilizer procurement and distribution policies, as well as direct support policies that the Nepal government may consider. While support policiessuch as subsidies may encourage increased utilization of fertilizers, policies that lower barriers to private sector entry and increase the density of fertilizer retailers could also increase fertilizer utilization.